Peningkatan literasi keuangan siswa melalui penggunaan media interaktif SIKU (Sikapi Uangmu) - Holpi Fikria Nanda; Dwi Iga Luhsasi; Destri Sambara Sitorus (Jurnal Inspirasi Pendidikan, 2023)
For students to have the tools to manage their finances, they have to be taught about financial literacy from an early age wisely. The purpose of this research is to help senior high school students improve financial literacy through interactive media SIKU (Sikapi Uangmu). This research used a Quasi-experimental group experimental design with a Nonequivalent control group type. Samples were taken using total sampling techniques in 2 different classes. Class X IIS 2 was the experimental group, and Class X IIS 3 was the control group. The research data was taken using test instruments. The data that has been collected is then analyzed using a t-paired test. The results showed that the use of SIKU interactive media for senior high school students was able to increase student's financial literacy. Paired t-test testing which produces a significance of 0.000, t=-12.43, explains the increase in financial literacy of learning using SIKU. These results show that SIKU interactive media can be applied in the learning process in schools, and effectively contribute to improving students' financial literacy.